2022
DOI: 10.1186/s12885-022-09902-9
|View full text |Cite
|
Sign up to set email alerts
|

Is RDW a clinically relevant prognostic factor for newly diagnosed multiple myeloma? A systematic review and meta-analysis

Abstract: Background Multiple myeloma (MM) is an incurable plasma cell malignancy. Red cell distribution width (RDW) is a prognostic marker in various diseases, solid tumors, and hematologic neoplasms, but its prognostic significance in MM is controversial. In this study, we aimed to assess the relationship between RDW and the clinical prognosis of MM patients through a meta-analysis. Methods Relevant literature were retrieved from PubMed, Embase, and Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Elevated RDW has been associated not only with vascular risks, but also with the prognosis and risks of complications of various cancers, such as breast, lung, and esophageal cancers [44][45][46][47][48]. Recently, RDW has been reported as a potentially useful biomarker to predict prognosis and complication risks in hematologic cancers, such as diffuse large B-cell lymphoma, primary central nervous system lymphoma, multiple myeloma and chronic myeloid leukemia [49][50][51][52][53]. The limitations of our study include its single-center, retrospective design involving patients with heterogenous backgrounds and potential confounding factors that may have affected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW has been associated not only with vascular risks, but also with the prognosis and risks of complications of various cancers, such as breast, lung, and esophageal cancers [44][45][46][47][48]. Recently, RDW has been reported as a potentially useful biomarker to predict prognosis and complication risks in hematologic cancers, such as diffuse large B-cell lymphoma, primary central nervous system lymphoma, multiple myeloma and chronic myeloid leukemia [49][50][51][52][53]. The limitations of our study include its single-center, retrospective design involving patients with heterogenous backgrounds and potential confounding factors that may have affected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other authors confirmed the role of RDW in predicting outcome of MM patients, in short- and long-distance 16 , 17 , and still others hypothesized a role of this erythrocyte index in prediction of clinical response to treatment 18 , 19 . Moreover, a recent systemic review and a meta-analysis of all publications regarding the trend of RDW in multiple myeloma was carried out, with the conclusion that this index is a significant predictor of outcomes in new diagnosed multiple myeloma patients 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] To date, increasing evidence has shown that RDW is associated with worse outcomes in many diseases, including acute exacerbation of chronic obstructive pulmonary disease, COVID-19, multiple myeloma, heart failure, spontaneous intracerebral hemorrhage, and community-acquired pneumonia. [12][13][14][15][16][17] Recently, Deniz et al 18 revealed the significant predictive value of RDW in mortality among ICU patients. However, the relationship between RDW and outcome of patients with VAP remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that RDW is associated with aging, inflammation, oxidative stress, nutritional deficiency, erythropoiesis impairment, and telomere shortening 8–11 . To date, increasing evidence has shown that RDW is associated with worse outcomes in many diseases, including acute exacerbation of chronic obstructive pulmonary disease, COVID‐19, multiple myeloma, heart failure, spontaneous intracerebral hemorrhage, and community‐acquired pneumonia 12–17 . Recently, Deniz et al 18 revealed the significant predictive value of RDW in mortality among ICU patients.…”
Section: Introductionmentioning
confidence: 99%